WEWENANG OMBUDSMAN REPUBLIK INDONESIA MENURUT UNDANG-UNDANG NOMOR 25 TAHUN 2009 - Kurniawati, Aprillia; Beni Hidayat (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2023)
Public Service is an activity to meet service needs in accordance with laws and regulations. Supervision of the delivery of public services is carried out by internal supervisors and external supervisors. Internal supervision is carried out by direct superiors in accordance with laws and regulations. Meanwhile, external supervision is carried out by the ombudsman, the community, the DPR, the DPRD, and the District/City DPRD. The research method in this paper uses normative legal methods. The normative legal method is a scientific research procedure to find truth based on scientific logic from the normative side through a statutory approach (statue approach), supported by secondary data by collecting literature study data using qualitative descriptive analysis. The Ombudsman was first born in Indonesia based on Presidential Decree Number 44 of 2000 and became a demand of the reform era to create a clean, transparent and corruption-free government .